Investigation of manifestation of optical activity in anisotropic crystals - Konstantinova, A.; Evdişcenco, E.; Kaldîbaev, K.; Imangazieva, K.; Konstantinov, C. (Moldavian Journal of the Physical Sciences, 2005)
The special features of the manifestation of optical activity in the anisotropic absorbing